Interfacial mechanism for efficient resistive switching in Ruddlesden-Popper perovskites for non-volatile memories - Solanki, Ankur (2020)
Ion migration, one origin of current-voltage hysteresis, is the bane of halide perovskite optoelectronics. Herein, we leverage this unwelcome trait to unlock new opportunities for resistive switching using layered Ruddlesdsen-Popper perovskites (RPPs) and explicate the underlying mechanisms. The ON/OFF ratio of RPP-based devices is strongly dependent on the layers and peaks at n̅ = 5, demonstrating the highest ON/OFF ratio of ∼104 and minimal operation voltage in 1.0 mm2 devices. Long data retention even in 60% relative humidity and stable write/erase capabilities exemplify their potential for memory applications. Impedance spectroscopy reveals a chemical reaction between migrating ions and the external contacts to modify the charge transfer barrier at the interface to control the resistive states. Our findings explore a new family of facile materials and the necessity of ionic population, migration, and their reactivity with external contacts in devices for switching and memory applications.